The influence of Si/Al ratios of synthesized beta zeolites for the alkylation of isobutane with 2-butene - Yoo, K; Smirniotis, PG (ELSEVIER, 2002)
Alkylation of isobutane with 2-butene was performed in the liquid phase at 80degreesC over beta zeolites with Si/Al ratios ranging from 6 to 30. Two different feeds (isobutane/2-butene molar ratios of 20 and 98) were utilized with the same olefin WHSV of 0.5 h(-1) to investigate the influence of feed compositions as well. The zeolites used in this study were synthesized directly in order to minimize the variations in structural characteristics such as crystallinity, BET area and pore volume. The relative hydrogen transfer activity of zeolites was determined using the n-hexane cracking reaction, The hydrogen transfer activity remains almost constant for zeolites; with Si/Al ratios up to 15 and then decreases with any increase in Si/Al ratio. In contrast to the common belief that a higher aluminum content zcolite is more stable for this reaction, we observed optimum Si/Al ratios of beta zeolites. This unexpected result can be attributed to the existence of an optimal level of acidity, which minimizes the formation of heavy carbonaceous materials that deactivate the catalysts. With the loss of hydrogen transfer activity, bulky carbonaceous materials causing the deactivation of zeolite were formed by poly/oligomerization inside zeolite catalysts. Moreover, we found that the cracking activity plays some role in prohibiting the formation of these heavy materials. The result of this study indicates that both high hydrogen transfer capability and cracking activity are needed to maintain the stability of zeolite catalysts during alkylation. It is also observed that a significant change in selectivity of TMPs can be effected by changing feed conditions. (C) 2002 Elsevier Science B.V. All rights reserved.
Keywords: TEMPERATURE-PROGRAMMED DESORPTION; HYDROGEN-TRANSFER; PROCESS VARIABLES; ULTRASTABLE Y; ACIDITY; CATALYSTS; CRACKING; BUTENE